KEMAMPUAN BERPIKIR KREATIF DALAM PENGAJUAN MASALAH PADA MATERI PERSAMAAN LINEAR SATU VARIABEL DI SMP - Meyta Rahayu; Yulis Jamiah; Silvia Sayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this study is to describe student’s creative thinking abilities of problem posing in linear equation of one variable at SMP Negeri 3 Pontianak. The specific purpose is to describe student’s creative thinking abilities in fluency, flexibility and novelty of problem posing, and level of student’s creative thinking abilities of problem posing. The research method used is a descriptive method with the survey form of studies. The research agency is students of Class VIII H in SMP Negeri 3 Pontianak. The data collection techniques used are written tests and interviews. The results showed that student’s creative thinking abilities of problem posing from 30 students there were 16 students who could meet the fluency indicator, 8 students who could meet the flexibility indicator and 13 students who could meet the novelty indicator. The level of creative thinking ability of 30 students, there are 3 students at level 4, 8 students at level 3, 7 students at level 2, 6 students at level 1, 6 students at level 0.Keywords: Creative Thinking Ability, Linear Equation Of One Variable, Problem Posing.